Dr. Carlos Manuel Miyares Cao, an example of an outstanding doctor - Ernesto Miyares Díaz (Universidad de Ciencias Médicas de La Habana, 2021)
José Martí said: "Knowing how to sacrifice is the price of lasting success for everything". The working life of Dr. Carlos Manuel Miyares Cao is summed up in great sacrifice and success.  He was an outstanding doctor who knew how to link his administrative responsibilities to research and development and medical care. As a tireless fighter for the advances of medicine, he was the founder of the Cuban School of Pharmacology and a notable example for Cuban and Latin American doctors. During his student life, he collaborated with important activities that took place at his time, being founder of the revolutionary militias. During his medical studies, he was a founder member of the University Militias "José Antonio Echeverría".  Wearing the symbolic red wine shirt, gray pants and black beret, he paraded on November 27, 1959 from the university to the Punta esplanade to pay tribute to the 8 medical students. One of his most fraternal fellow students says, "... I remember him very clearly; he was tall and because of his height he was among the ranks of the final lines; with his rifle he used to march with the discipline that characterized him during all his life." With his words, he illustrated the principles and convictions that marked his existence. After the resignation of university professors, Dr. Miyares was appointed among the first undergraduate Pharmacy instructors at the Department of Pharmacology of the School of Medicine of the University of Havana.  He was also the founder of the AJR (Association of Young Rebels) and the UJC (Union of Young Communists) in the university. He had the privilege to be one of the first graduates after de triumph of the Revolution.  His graduation, which was held at Pico Turquino in eastern Cuba, was presided by Fidel Castro in 1965.